2020
DOI: 10.1002/pa.2462
|View full text |Cite
|
Sign up to set email alerts
|

Management information systems and the quality of financial statements in local government

Abstract: Accountability and transparency of public institutions at both central and local levels is a phenomena which is a major issue these days. The demand for a form of providing information and on government financial activities and performance to the public is a form of accountability and transparency. This study aims to determine the effect of the adoption of Government Accounting Standards, Utilization of SIMDA, and Obedience to Regulations on the Quality of Financial Statements. The study population is the fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…They also need reliable, varied and relevant information in their decision-making efforts. Yuesti et al, (2020) have the opinion that "public sector accounting has a central role in providing financial reports as a form of implementing public accountability." Accounting and financial reports have the meaning of a process of collecting, processing and communicating information that has uses in decision making and for assessing the performance of an organization (Yuesti et al, 2020).…”
Section: Moral Hazardmentioning
confidence: 99%
“…They also need reliable, varied and relevant information in their decision-making efforts. Yuesti et al, (2020) have the opinion that "public sector accounting has a central role in providing financial reports as a form of implementing public accountability." Accounting and financial reports have the meaning of a process of collecting, processing and communicating information that has uses in decision making and for assessing the performance of an organization (Yuesti et al, 2020).…”
Section: Moral Hazardmentioning
confidence: 99%
“…Therefore, information needs in the public sector are more varied, information is not limited to financial information produced from the organization's accounting system. Nonmonetary information such as service performance must also be considered in decision-making (Yuesti et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, built around institutional theory, Han (2020) stated that deficits in information provision, assessment, and consequence can relatively affect the success or failure of federal agency performance accountability. In light of the information provision and assessment, Yuesti et al (2022) found the positive effect of conforming to government accounting standards, adopting government information systems, and complying with regulations regarding the quality of financial statements and performance of local governments. Given the relative void in the efficacy of information system quality towards the quality of performance accountability, more studies to unveil the factors should be warranted.…”
Section: Introductionmentioning
confidence: 99%